Thyroid carcinoma with thymus-like differentiation (CASTLE) tumor: а сase report - A. A. Ilyin; V. V. Polkin; P. A. Isaev; F. E. Sevrukov; N. Yu. Dvinskych; M. I. Ryzhenkova; S. A. Ivanov; A. D. Kaprin (Опухоли головы и шеи, 2021)
Thyroid carcinoma with thymus-like differentiation (Carcinoma Showing Thymus-Like Differentiation, CASTLE) is an extremely rare disease. It arises from the thymus tissue ectopic into the tissue of the thyroid gland, usually in patients 40–50 years old. In this work, we present an observation of the development of CASTLE in a patient at a young age. A 21-year-old woman was admitted to our clinic with a volumetric education in the projection of the left lobe of the thyroid gland. Ultrasound revealed a 5-centimeter thyroid tumor. Surgery was performed in the scope of thyroidectomy, selective cervical dissection (level VI). Morphological and immunohistochemical studies showed that cancer has a thymus-like differentiation (CASTLE). After 32 months, she recurred to the lymph nodes of the neck (level IV on the left). She underwent repeated surgery, after which she was observed without signs of relapse for 120 months. The rarity of the pathology leads to difficulties in establishing a diagnosis at the preoperative stage and in choosing the optimal treatment tactics during treatment and further follow-up.